Cardiorespiratory Monitoring during Neonatal Resuscitation for Direct Feedback and Audit - van Vonderen, Jeroen J.; van Zanten, Henriëtte A.; Schilleman, Kim; Hooper, Stuart B.; Kitchen, Marcus J.; Witlox, Ruben S. G. M.; te Pas, Arjan B. (Frontiers in Pediatrics, 2016)
Neonatal resuscitation is one of the most frequently performed procedures and it is often successful if the ventilation applied is adequate. Over the last decade, interest in seeking objectivity in evaluating the infant’s condition at birth or the adequacy and effect of the interventions applied has markedly increased. Clinical parameters such as heart rate, colour and chest excursions are difficult to interpret and can be very subjective and subtle. The use of ECG, pulse oximetry, capnography and respiratory function monitoring can add objectivity to the clinical assessment. These physiological parameters, with or without the combination of video recordings, can be used directly to guide care, but can also be used later for audit and teaching purposes. Further studies are needed to investigate whether this will improve the quality of delivery room management. In this review we will give an update of the current developments in monitoring neonatal resuscitation.